Real-Time Shading. - Olano, Marc (CRC Press, 2002)
This book covers real-time shading systems, their design and how they work. Procedural shading, long valued for off-line rendering and production animation is now possible on interactive graphics hardware. These developments are important for areas such as game development, product design, and scientific visualization, among others. The authors include examples of techniques for achieving common effects efficiently in a real-time shading language ranging from full procedural shading on advanced specialized hardware to limited, yet surprisingly flexible shading on unextended OpenGL, to modern P.